2012
DOI: 10.4103/0301-4738.98701
|View full text |Cite
|
Sign up to set email alerts
|

Ranibizumab as an adjunct to laser for macular edema secondary to branch retinal vein occlusion

Abstract: Purpose:To compare the safety, efficacy, and dosing regimen of intravitreal ranibizumab as an adjunct to laser therapy for the treatment of macular edema secondary to branch retinal vein occlusion (BRVO).Materials and Methods:Thirty eyes of 30 patients of BRVO of at least 6 weeks duration were randomized into three groups: Group 1 received grid laser treatment alone, Group 2 received a single dose of intravitreal injection of ranibizumab (0.5 mg / 0.05 ml) followed by grid laser treatment on 7th day following … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 3 publications
0
8
0
Order By: Relevance
“…Three trials were excluded because these were extension studies 15 28 29 and three trials were excluded because they evaluated only one treatment of interest. 24 30 31 Manual searching identified three further trials (BRIGHTER, 32 COMRADE-B 33 and VIBRANT 12 ).…”
Section: Resultsmentioning
confidence: 99%
“…Three trials were excluded because these were extension studies 15 28 29 and three trials were excluded because they evaluated only one treatment of interest. 24 30 31 Manual searching identified three further trials (BRIGHTER, 32 COMRADE-B 33 and VIBRANT 12 ).…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the group recommended careful observation with frequent follow-up examinations and prompt PRP of eyes in which neovascularization develops [33]. Recently, there have been several reports of the beneficial effects of combination therapy with laser and intravitreal anti-VEGF injections on improving VA [92,93]. This combination also provides durable response with less therapeutic interventions.…”
Section: Surgical and Laser Management Of Rvomentioning
confidence: 99%
“…Pars plana vitrectomy with internal limiting membrane peeling has also been investigated for treatment of RVO-associated macular edema with variable outcomes [50,74,91,92,93,94,95,96,97,98,99,100,101,102,103,104]. There is a need for further documentation of the effectiveness and safety of these therapies via randomized, controlled clinical trials, particularly in the era of effective and less invasive intravitreal pharmacotherapies.…”
Section: Surgical and Laser Management Of Rvomentioning
confidence: 99%
“…While focal and grid laser photocoagulation is routinely used to supplement anti-VEGF injections, the possible benefit of this combined treatment has not been thoroughly studied. It has been suggested that the addition of grid laser photocoagulation to anti-VEGF therapy to treat edema in BRVO can lead to a better visual outcome and decrease the number of injections needed than if laser was not utilized [ 19 , 20 ]. A separate prospective investigation found that the addition of a dexamethasone intravitreal implant to anti-VEGF injections also leads to a decrease in the number of injections needed and better vision in the combination group compared to monotherapy [ 21 ].…”
Section: Introductionmentioning
confidence: 99%